2016
DOI: 10.1002/2016jd025467
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and seasonal variations of secondary organic aerosol from terpenoids over China

Abstract: A majority of global secondary organic aerosol (SOA) comes from terpenoids. In this study, we carried out a 1 year nationwide observation of pinenes (α‐ and β‐pinene) and SOA tracers from monoterpenes (SOAM) and β‐caryophyllene (SOAC) over China for the first time. SOAM and SOAC tracers ranged from 9.80 to 49.0 ng m−3 and 1.72 to 7.72 ng m−3, respectively, with high levels in southern China. Pinenes ranged from 34 to 102 parts per trillion by volume, with α‐pinene dominant over β‐pinene. SOAM tracers were corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 97 publications
(166 reference statements)
5
34
2
Order By: Relevance
“…The annual average concentration 440 of the total M-SOA tracers was 59.3±24.6 ng m -3 (Table 1). The concentration of M-SOA tracers was higher than those reported in the previous studies from the urban site in Kunming (annual average: 44.1 ±38.8 ng m -3 ) (Ding et al, 2016b), three cities (Ohio, Michigan and California) in North America (summer: 30.4-60.6 ng m -3 ) (Stone et al, 2009) and a forest site in Hyytiä lä , Europe (summer: 15.1-33.3 ng m -3 ) .…”
Section: Terpene Soa Tracerscontrasting
confidence: 49%
“…The annual average concentration 440 of the total M-SOA tracers was 59.3±24.6 ng m -3 (Table 1). The concentration of M-SOA tracers was higher than those reported in the previous studies from the urban site in Kunming (annual average: 44.1 ±38.8 ng m -3 ) (Ding et al, 2016b), three cities (Ohio, Michigan and California) in North America (summer: 30.4-60.6 ng m -3 ) (Stone et al, 2009) and a forest site in Hyytiä lä , Europe (summer: 15.1-33.3 ng m -3 ) .…”
Section: Terpene Soa Tracerscontrasting
confidence: 49%
“…Considering that various uncertainties are associated with the approach of Kleindienst et al [39], as also indicated by these authors and in other publications since then [3,43,44,46], we estimate that the uncertainty that is associated with the SOC M and SOC I contributions to the OC is at least a factor of 2.…”
Section: Contribution Of the Measured Organic Compounds And α-Pinene mentioning
confidence: 98%
“…Considering that the annual average OC at the 12 sites ranged from 22 to 54 µgC/m 3 , this means that the percentages of SOC M and SOC I in OC were only around 1% each. Ding et al [46] also noted that biogenic SOC was elevated from April to September and was lowest in January and February, and that its composition changed dramatically from a monoterpene majority in fall-spring to an isoprene majority in summer. The authors further stated that the relative standard deviations were 53% for SOC M and 47% for SOC I and that because of various other uncertainties involved in the approach, their results should have underestimated the total amount of biogenic SOC in the air in China.…”
Section: Contribution Of the Measured Organic Compounds And α-Pinene mentioning
confidence: 99%
See 1 more Smart Citation
“…In polluted regions, the increase in O 3 levels due to high emissions of NO x and VOCs likely results in significant SOA formation via the ozonolysis of BVOCs (Sipilä et al, 2014;Riva et al, 2017). In addition, the large emission and formation of anthropogenic organic matter (OM) in urban areas enhance the incorporation of BVOC oxidation products into the condensed phase (Donahue et al, 2006). Recently, Carlton et al (2018) found that the removal of anthropogenic emissions of NO x , SO 2 , and primary OA in the Community Multiscale Air Quality Model (CMAQ) simulations could reduce BSOA by 23 %, 14 %, and 8 % in summertime, respectively.…”
Section: Introductionmentioning
confidence: 99%